A lanthanide based sensor for the time-gated detection of hydrogen sulfide. - Tropiano, M; Faulkner, S (Royal Society of Chemistry, 2014)
A kinetically stable Eu(III) complex for the detection of sulfide in water is reported. The probe shows excellent selectivity and fast reaction time. Its long-lived luminescence makes this the first probe for the time-gated detection of sulfide in complex biological samples.